Effect of traffic volumes on polycyclic aromatic hydrocarbons of particulate matter: a comparative study from urban and rural areas in Malaysia - Al-Battawi, Samer; Latif, Mohd Talib; How, Vivien; Thilakavathy, Karuppiah; Abd Hamid, Haris Hafizal; Tan, Chung Keat; Ho, Yu Bin (Public Library of Science, 2024)
Motor vehicles emit most Malaysian PAHs in particulate matter of 2.5 μm (PM2.5-bound PAHs). Although traffic-related air pollution harms healthy people, there is a knowledge gap regarding PAHs’ effects on Malaysians. This study examines PM2.5-bound PAH concentrations, distribution, sources, and health risks in Malaysia’s high and low-traffic zones. Kuala Lumpur (KL) and Hulu Langat (HL) exhibit Malaysia’s high- and low-traffic areas. The high-volume air sampler collected 40 ambient PM2.5 samples at both locations. Solid-phase extraction and gas chromatography-mass spectrometry (GC-MS) assessed PAHs. The mean PM2.5-bound PAH concentrations in KL (5.85 ng m-3) were significantly higher than in HL (0.55 ng m-3) (p<0.001). KL has nine times more low-molecular-weight PAHs (LMW-PAHs) (2.63 vs. 0.27 ng m-3) and eleven times more high-molecular-weight PAHs (HMW-PAHs) (3.22 vs. 0.28 ng m-3) than HL. Over 51% of PM2.5 air samples at both sites included HMW-PAHs. Source apportionment tools (Diagnostic ratio, positive matrix factorization, and principal component analysis) showed that fossil fuel combustions (petrol and diesel) produced the greatest PAHs in both locations. Moreover, PAH exposure impinged higher carcinogenic health risks in KL than in HL. In conclusion, traffic and automobile pollution account for the short- and long-term health risks posed by PAHs in both regions.